Study the Interaction Adsorptive Behavior of Sunset Yellow Dye and Loratadine Drug: Kinetics and Thermodynamics Study - Hiawi, Furat A.; Ali, Inaam H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The performance of drug treatment and assessments of different drugs' side effects both can be affected by the interaction between food additives and drugs. Organic compounds such as food colorants dyes are utilized as additives in a wide range of foods. In this study, the adsorption interaction behavior between the colorant food dye sunset yellow (SY) and the drug loratadine was examined. The adsorption procedure is conducted at different drug dosages, various SY dye concentrations, and different temperature (288-318K). The equilibrium data were explained by using Freundlich and Langmuir adsorption isotherms, but Langmuir offering the best fit model. Kinetics adsorptive behavior of sunset yellow on loratadine matched pseudo-second order kinetics. Thermodynamics study show that the process is exothermic, spontaneous and the disorder at the solid-solution interface was proven from the negative entropy (-140.556 J/ K.mol) of adsorption process.